Social Customer Journey Map: A Research on Communication Agencies - Işık Özkan; Cudi Kaan Okmeydan (Türkiye İletişim Araştırmaları Dergisi)
The aim of this study is to obtain in-depth information about the knowledge and experience of communication agencies regarding the concept of social customer journey. Based on a phenomenological research pattern, semi-structured interviews were conducted with eleven experts working in communication agencies operating throughout Turkey. Then, the themes emerging throughout the study were subjected to descriptive analysis. The findings revealed that agency-brand cooperation is extremely important in the planning process of social customer journey. It was determined that the agencies visualized the process by creating a customer journey map at the planning stage. In addition, it has been determined that all the problems that customers may encounter during the planning stage have been foreseen and solutions have been produced. Findings also reveal that communication agencies tracked customer movements on social media to provide a better experience to customers. Utilizing various online tracking and reporting software, these agencies monitored websites and received reports about consumer behaviour. Findings also demonstrate that it has become a necessity for agencies and brands to invest in Artificial Intelligence- powered automation systems in order to provide a better experience to customers and maximize interaction.